DAYA DUKUNG LAHAN UNTUK PENGEMBANGAN PETERNAKAN KAMBING POTONG DI KABUPATEN DELI SERDANG MENGGUNAKAN TEKNOLOGI GEOGRAPHIC INFORMATION SYSTEM (GIS) - Irwan Prasetyo; Irawadi; Zefri (Fakultas Teknik Universitas Krisnadwipayana, 2024)
Deli Serdang Regency has several types of livestock developed by the community in supporting food security in the district. This research was conducted to analyze the carrying capacity of land use and formulate directions and strategies for the development of goat farms in Deli Serdang Regency. Data collection was carried out using survey, observation, and data collecting methods. The data obtained was analyzed descriptively. Landuse in Deli Serdang Regency is generally suitable for the development of goat farming. Land use that has the potential for the development of goat farming is land cultivated in the agricultural sector such as plantations/gardens, dry fields/fields, and paddy fields. Existing land uses that can currently be used for the development of goat farming in the Deli Serdang district are shrubs (10,784.99 ha), dry fields/fields (18,091.18 ha), rice fields (32,421.42 ha), plantations/gardens ( 129,018.11 ha), and Forest (43,731.41 ha). Directions for the development of goat farming are directed at optimizing the potential of natural resources, especially the use of forage for animal feed. Livestock development can be directed at land use classes in the form of shrubs converted into grazing land for planting superior forage, so that the carrying capacity increases for the cultivation of goat farming. Directions for the Development of Goat Farming can be directed based on the RTRW of Deli Serdang Regency, namely agricultural areas (food crops, horticulture, and plantation areas) which can be applied in almost all areas of the sub-district. The development of goat farming in Deli Serdang Regency should pay more attention to the potential of land resources as a place to raise livestock so that the carrying capacity of the feed will be fulfilled.